Study of Ionospheric Irregularities in the F-region During Geomagnetic Storms (Global Journal of Science Frontier Research, 2017)
The study of horizontal movements of small scale ionospheric irregularities at Waltair (dip 17.70 N; 83.30 E) using D1 technique was started as early as I.G.Y. period. In this paper the results of observations of the drift and anisotropy parameters of ionospheric irregularities in the F-region during 6 Geomagnetic storms are presented. F-region spaced antenna drift records taken on frequency 5.6 MHz during the period September 1983-May 1984 at Waltair (Visakhapatnam) are used in the present investigation. In F-region, the true drift velocity during the entire storm period is found to be smaller than the average value of the control day true drift velocity. The random velocity during storm time is comparatively more than that observed on control days, at least for about 40 hrs after the commencement of the storm. The orientation of the semimajor axis mostly lies in the range of 900 – 1500 N of E, both on storm days as well as on control days, indicating no significant change during storm days.
Keywords: close spaced receivers; ground diffraction pattern; ionospheric irregularities and geomagnetic storm